2006
DOI: 10.4103/0028-3886.24711
|View full text |Cite
|
Sign up to set email alerts
|

Carotid artery stenting: Results and long-term follow-up

Abstract: CAS is an effective treatment modality of symptomatic carotid artery disease but should be carefully done in high-risk groups having severe medical ailments and those having severe bilateral stenosis of the carotid arteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…[16][17][18] The data on the rate of periproce-dural complications amongst Indian patients during CAS is scarce. One study by Gupta et al 19 reported a periprocedural mortality rate of around 8. 1% and minor stroke of about 4.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18] The data on the rate of periproce-dural complications amongst Indian patients during CAS is scarce. One study by Gupta et al 19 reported a periprocedural mortality rate of around 8. 1% and minor stroke of about 4.…”
Section: Discussionmentioning
confidence: 99%
“…Gupta et al (2006) describe such a case in an adult with good outcome [18]. Other authors consider the indications to early and delayed exploration giving examples of effects of the presence of bony fragments or foreign agents retained within the vertebral canal [19, 29, 54, 66, 70].…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
“…Higher rates of combined death and stroke (12%) were reported by Gupta and his colleagues in their initial 48 procedures. 12 However, this group did not use distal protection devices in most of their procedures, which is thought to be advantageous in preventing the periprocedural stroke in CAS. 7 To date, Stenting and Angioplasty with Protection in Patients at High Risk for Endarterectomy (SAPPHIRE) 7 is the only randomized trial that showed the superiority of CAS over CEA in reducing the rates of perioperative death and stroke (12.6% for CEA and 5.8% for CAS) and death, stroke, or myocardial infarction (7.3% for CEA and 2.6% for CAS) when used in high-risk patients.…”
Section: Survivalmentioning
confidence: 99%